Domestic Investment Laws and International Economic Law in the Liberal International Order. Issue 1 (February 2023) - Chaisse, Julien; Dimitropoulos, Georgios
Abstract: International Economic Law (IEL) has largely regulated cross-border trade and investment in the post-WWII world. IEL has become an important part of the Liberal International Order that prescribes a set of rule-based relationships for international cooperation based on political liberalism, economic liberalism, and liberal internationalism. However, economic globalization has witnessed a relative decline, especially after the 2008 global financial crisis and the COVID-19 pandemic. This form of 'de-globalization' challenges the assumptions upon which modern IEL is premised. This introductory article to the special issue on 'Domestic Investment Laws and International Economic Law in the Liberal International Order' explains how domestic law has started playing an increasingly important role in regulating foreign investment. Often overlooked instruments such as Domestic Investment Laws, Investment Screening Mechanisms, and Investment Promotion Agencies are now important tools in promoting or restricting foreign investment flows. Expanding on this premise, the article examines the transition from international to domestic in the Liberal International Order with a focus on Domestic Investment Laws. The move to domestic law does not signal a new era of economic isolation for States. Instead, it presents an effort to achieve similar ends of attracting foreign investors using different means while exercising more control over foreign investment.